AN EXAMINATION OF THE IMPLEMENTATION OF INTERNET OF THINGS IN HEALTHCARE UTILIZING SMARTWATCHES - Boshrabadi, Fatemeh Sadeghi; Abolhassani, Moussa; Shafaghi, Shadi; Ghorbani, Fariba; Shafaghi, Masoud (Universitas Airlangga, 2024)
Background: Smartwatches can use sensors to collect and send data to medical teams and family members through the platform of the Internet of things (IoT). The data are first analysed on the platform and the final results are used by the medical team. Aims: This paper reviews and categorises studies conducted in the field of the Internet of things based on smartwatches. Methods: The covered papers have been published over 13 years from 2010 to 2022. The search yielded 227 papers out of which 43 papers were reviewed after screening. The search keywords were “wearables, internet of things, smartwatches, smart bracelet, healthcare, and disease”. The search covered databases including PubMed, ScienceDirect, and IEEE. Results: Smartwatches are used in three fields of healthcare, including palliative care, speech therapy, diagnosis, disease prevention, rehabilitation, and health improvement. Conclusion: Smartwatches are not free of drawbacks and have not received the attention they deserve in the healthcare field. Given the potential of smartwatches, they can be useful in the health sector. Keywords: Disease, IOT, Smartwatch, Wearable